Können Kinder zu Beginn der ersten Klasse bereits mit statistischen Daten argumentieren? – Empirische Befunde aus einer Interviewstudie im Anfangsunterricht (mathematica didactica, 2020)
To what extent are children able to develop data-based arguments already at the beginning of their school career? In an interview study with first-graders at the very beginning of their first year in primary school, we investigated to what extent they are able to engage in argumentation based on statistical data. The results show that all participants were able to develop at least one own argument based on given statistical data. The qualitative analysis of the students’ responses provides insights into potential difficulties children face when developing data-based arguments and, therefore, leads to implications on how children can be fostered in this regard in the elementary classroom.